The Implementation of Preparing Test Items for the Elements of the Arabic Language (Phonology, Vocabulary, and Structures)/ تطبيق إعداد بنود الإختبار لعناصر اللغة العربية ( الأصوات والمفردات والتراكيب ) - Maftuhati Maftuhati; Nihayatin Musyafa'ah; Silmi Maulidya (Al-Arabi: Jurnal Bahasa Arab dan Pengajarannya = Al-Arabi: Journal of Teaching Arabic as a Foreign Language, 2021)
The purpose of writing this article is to implement test item preparation for language items. There are three types of this test: sounds, structures, and vocabulary. We also know that preparing test items has a very important role, because every subject need testing. Every teacher, of course, needs to practice preparing test items so that the tests offered are suitable for educational goals. The steps for writing the test items or questions include: (1) setting goals, (2) preparing the criterion questions, (3) writing the question items, (4) browsing the questions, (5) experiment, (6) analyzing the question items, (7) improving the test, (8) compiling test, (9) take the test, (10) interpret the test results. In this article, the researcher writes only three steps, which is from setting goals to applying writing questions.الهدف بكتابة هذه المقالة لتطبيق إعداد بنود الإختبار  لعناصر اللغة. ومن أنواع هذا الإختبار هناك ثلاث إختبارات وهي: الأصوات، والتراكيب، والمفردات. كما عرفنا أنّ إعداد بنود الإختبار لها دور مهم جدا، لأن لكل المادة تحتاج إلى الإختبار. فلكل المعلم فطبعا يحتاج إلى ممارسة إعداد بنود الإختبار لكي الإختبارات المطروحة مناسبة بأهداف التعليمية. ومن الخطوات لكتابة بنود الإختبار أو الأسئلة منها: (1) تحديد الأهداف (2) اعداد المعيار الأسئلة (3) كتابة بنود الأسئلة (4) تصفّح الأسئلة (5) التجريبة (6) تحليل بنود الأسئلة (7) تحسّن الإختبار  (8) تجميع الإختبار (9) إجراء الإختبار (10) تفسير نتائج الإختبار . وفي هذه المقالة كتابة الباحثة فقط ثلاث خطوات وهو من تحديد الأهداف حتى تطبيق كتابة بنود الأسئلة.